Rozwój oka u dzieci. Część I. Wymiary gałki ocznej - Lachowicz, Ewelina; Czepita, Damian (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The aim of an article is to introduce and elaborate on the available literature concerning eyeball development. Material and methods: The information content in the article comes from studies performed on groups of children of different ages. In some analysis study groups were chosen depending on sex. Axial length of the eye, depth of anterior chamber, lens’s thickness and vitreous’s dimension was defined. Results: Intensive changes of eyeball dimensions progress with age. A period of fast and slow growth of the eye can be discerned. Axial length of the eye, depth of anterior chamber, lens’s thickness and vitreous’s dimension increase over time. Growth of the axial length is mainly caused by increasing axial length of vitreous cavity. The increase in depth of the anterior chamber plays a lesser role. Girls tend to have shorter eyes compared with boys. Both age and male gender are associated with deeper anterior chambers and larger vitreous cavity. Lens thickness decreases with the growth of the eyeball. However gender does not play a role. Conclusions: Based on current literature, it is difficult exactly indicate what are the standards of eyeball growth in children and youths. To establish these parameters, further studies on the another examination in representative group of children and teenagers are necessary.